An efficient and mild access to N-acetyl protected purine nucleosides based on a chemoselective enzymatic hydrolysis - Palacio, Cyntia M. (2013)
N-Monoacetylated derivatives of ribo- (adenosine, guanosine) and 2′-deoxyribonucleosides (2′-deoxyadenosine and 2′-deoxyguanosine), useful as oligonucleotide building blocks, were obtained in 88–100% by enzymatic chemoselective hydrolysis of the corresponding peracetylated nucleosides. Among the tested hydrolases, most satisfactory results were found with acylase I from Aspergillus melleus and Candida antarctica lipase B. For acylase I, the observed chemoselectivity towards ester hydrolysis, without amide reaction, broadens the information about the selectivity of the enzyme and its synthetic applications in the field of nucleosides.